An Analysis of Character Education in “English for Nusantara” Textbook for Eight Grade Students - Tahrun; Indri Nurhasanah; Aty Hartati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This paper was to analyze character education principles embedded in the English textbook